2002
DOI: 10.1007/s00204-002-0381-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of metabolites in MDMA (ecstasy)-induced nephrotoxicity: an in vitro study using rat and human renal proximal tubular cells

Abstract: The metabolism of 3,4-methylenedioxymethamphetamine (MDMA, ecstasy) has recently been implicated in the mechanisms underlying ecstasy-induced neurotoxicity and hepatotoxicity. However, its potential role in ecstasy-induced kidney toxicity has yet to be investigated. Thus, primary cultures of rat and human renal proximal tubular cells (PTCs) were used to investigate the cytotoxicity induced by MDMA and its metabolites methylenedioxyamphetamine (MDA), alpha-methyldopamine (alpha-MeDA), and the glutathione (GSH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 36 publications
4
52
0
7
Order By: Relevance
“…Apparently at lower MDMA concentrations (Ͻ1 mM), insufficient metabolites are being formed to cause cytotoxicity in our in vitro system. This finding was also described by Carvalho et al (2002). At the highest MDMA concentration tested (4 mM), cytotoxicity was caused by MDMA itself, because phase I metabolism was completely inhibited by MDMA and no metabolites could be formed.…”
Section: Discussionsupporting
confidence: 81%
“…Apparently at lower MDMA concentrations (Ͻ1 mM), insufficient metabolites are being formed to cause cytotoxicity in our in vitro system. This finding was also described by Carvalho et al (2002). At the highest MDMA concentration tested (4 mM), cytotoxicity was caused by MDMA itself, because phase I metabolism was completely inhibited by MDMA and no metabolites could be formed.…”
Section: Discussionsupporting
confidence: 81%
“…We have also previously demonstrated that the metabolism is important for MDMA-induced toxicity to peripheral organs. [18][19][20] The underlying mechanisms of MDMA and MDA-induced neurotoxicity, namely the toxic effects mediated by its metabolite(s), remain to be completely elucidated. Herein we present cyclic voltammetry studies that provide evidence for a correlation between the toxicity of MDMA and MDAmetabolites and their redox potential.…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine was purchased from Merck (Darmstadt, Germany), MDMA and ryanodine were from Sigma Chemie (Deisenhofen, Germany), and pure, i.e., preservativefree, 2% SCh was from Curamed Pharma (Karlsruhe, Germany). Corresponding to MDMA concentrations applied in other nonperfused tissue preparations (Leonardi and Azmitia, 1994;Carvalho et al, 2002;Rusyniak et al, 2005), we used 100 to 1000 (4000) M.…”
Section: Methodsmentioning
confidence: 99%